Adaptive behaviour, executive function and employment in adults with Down syndrome. Issue 1 (7th December 2017) - Tomaszewski, B.; Fidler, D.; Talapatra, D.; Riley, K.
Abstract: Background: Individuals with Down syndrome (DS) demonstrate difficulties with aspects of executive function (EF) and adaptive behaviour across the lifespan. There is a current lack of information regarding how these difficulties relate to employment outcomes in adulthood. This study evaluated the adaptive behaviour and EF profiles of individuals with DS during early adulthood and the association between these areas of functioning and employment status. Methods: Parents or caregivers of primarily young adults with DS ( n = 31; mean chronological age = 25.9 years; SD = 5.92) completed the Vineland Adaptive Behavior Scales – Second Edition the Behavior Rating Inventory of Executive Function – Adult version and a demographic questionnaire that requested information regarding adult employment status. Results: Findings indicated a distinct pattern of relative strengths and challenges in adaptive behaviour and EF. In addition, the EF sub‐domain of working memory was a significant predictor of employment status. Conclusions: Specific aspects of the DS cognitive profile may have an important influence on employment status in primarily young adults with DS. Implications for interventions are discussed.